Uso de geotecnologia para análise da alteração da paisagem do alto curso da bacia hidrográfica do rio lontra entre os anos de 1985 a 2015. - ALVES, Hudson Damasio (Universidade Federal do Tocantins, 2023)
This work aims to build a prognosis of land use and occupation in the upper course of the Lontra river hydrographic basin, located in Araguaína in the north of the State of Tocantins. In this way, it was considered the applicability of geotechnologies that extend from environmental monitoring and analysis, as well as the acquisition of spatial information. For this research, images generated from 1985 to 2015 from the LANDSAT-5 satellite, TM sensor (Thematic Mapper), with a spatial resolution of 30 m were used. Subsequently, thematic classes were elaborated, being urban areas, pasture areas, temporary agriculture, continental water bodies, rural and forest formations, verified in the field. Armed with this prognosis, there were noticeable changes in the landscape of the area under study, between the years 1985 and 2015 the urban areas grew 504.65%, in contrast rural formations had a reduction of about 87.11%, In conclusion, the loss of training is significant, while urban areas and activities linked to temporary agriculture areas (141.11%) grew dramatically. The importance of geotechnologies for the analysis and understanding of the landscape is emphasized, with the purpose of making decisions in line with their weaknesses and potential.